Controlled synthesis of hierarchical CoxMn3−xO4 array micro-/nanostructures with tunable morphology and composition as integrated electrodes for lithium-ion batteries - Yu, Le (2014)
Hierarchical CoxMn3−xO4 array micro-/nanostructures with tunable morphology and composition have been grown on conductive stainless steel with robust adhesion by a facile solvothermal route and a subsequent annealing treatment. By simply controlling the volume ratio of components in the mixed solvent, the morphology of the products can be tailored from hierarchical nanowires to nanosheets. Benefitting from the unique structural features, the resultant CoMn2O4nanowires and MnCo2O4nanosheets exhibit excellent electrochemical performance with remarkable specific capacities (540–207 mA h g−1) at various current rates (1–10 C) and good cycling stability for highly reversible lithium storage. The enhanced electrochemical performance suggests their promising use as integrated binder-free electrodes for microscale lithium-ion batteries.